Blockade of AIM2 inflammasome or α1-AR ameliorates IL-1β release and macrophage-mediated immunosuppression induced by CAR-T treatment. Issue 1 (7th January 2021) - Liu, Dan; Xu, Xiyue; Dai, Yulian; Zhao, Xuan; Bao, Shunshun; Ma, Wen; Zha, Li; Liu, Shuci; Liu, Yuchen; Zheng, Junnian; Shi, Ming
Abstract : Background: Interleukin (IL) 1 released from monocytes/macrophages is one of the critical determinants in mediating the adverse events of chimeric antigen receptor T cell (CAR-T) therapy, including cytokine release syndrome and neurotoxicity. However, the molecular mechanisms of IL-1 production during CAR-T therapy remain unknown. Methods: The roles of AIM2 and α1-adrenergic receptor (α1-AR) in CAR-T treatment-induced IL-1β release were evaluated by gene silencing, agonist or antagonist treatment. The phenotype switch of macrophages in response to CAR-T treatment was analyzed concerning cytotoxicity of CAR-T cells and proliferation of activated T cells. Results: This study provided the experimental evidence that CAR-T treatment-induced activation of AIM2 inflammasome of macrophages resulted in the release of bioactive IL-1β. CAR-T treatment-induced α1-AR-mediated adrenergic signaling augmented the priming of AIM2 inflammasome by enhancing IL-1β mRNA and AIM2 expression. Meanwhile, tumor cell DNA release triggered by CAR-T treatment potentiated the activation of AIM2 inflammasome in macrophages. Interestingly, an apparent phenotypic switch in macrophages occurred after interacting with CAR-T/tumor cells, which greatly inhibited the cytotoxicity of CAR-T cells and proliferation of activated T cells through upregulation of programmed cell death-ligand 1 (PD-L1) and indoleamine 2, 3-dioxygenase (IDO) in the macrophages. Blockade of AIM2 inflammasome or α1-AR reversed the upregulation of PD-L1 and IDO and the phenotypic switch of the macrophages. Conclusion: Our study implicates that CAR-T therapy combined with the blockade of AIM2 inflammasome or α1-AR may relieve IL-1β-related toxic side effects of CAR-T therapy and ensure antitumor effects of the treatment.